(untitled) (International Journal of Built Environment and Sustainability, 2017)
Recent studies have emphasized the importance of the courtyard microclimate to the building and the need for a comparative study on their typology in other to ascertain the best alternative. Also emphasizing that the architect choice of the courtyard typology to be adopted in his architectural design schemes should be based on performance rather than his mere intuitive choice. Therefore, an investigational study of two different courtyard forms with the same perimeter, and material finished -the fully enclosed internal central courtyard and the semi-enclosed courtyard has been carried out in two existing residential buildings, in the city of Kafanchan-Nigeria. The main purpose of the study is to compare their climatic performances in other to ascertain the best option. The study employed the experimental methodology. Three Hobo Weather Data Loggers (HWDL) were used to collect data in the courtyards, and the third one was positioned in the outdoor area as a benchmark. Only two climatic variables, namely air temperature, and relative humidity were examined as these variables have not been investigated in a single research on the courtyard in Nigeria. The results showed a definite difference in the microclimatic conditions of the two courtyards. The fully enclosed internal courtyard is seen to have a better air temperature difference of 1oc to 3oc at the time intervals, and the relative humidity difference of 1% to 6%. In conclusion, the fully enclosed internal courtyard has demonstrated a more favorable microclimatic performance than the semi-enclosed, and future simulation studies towards its optimization are recommended.